Measuring the potential impacts of improved food-feed crops: methods for ex ante assessment - Thornton, Philip K.; Kristjanson, Patricia M.; Thorne, Peter J. (Elsevier, 2003)
The recent increased emphasis on impact assessment is due in part to the rapidly changing nature of funding for agricultural research and the shifts that have occurred in what is expected of the agricultural research community. The reasons for doing impact assessment are relatively clear: ex post studies can determine the impact of past investment in research on target beneficiaries and are a way to learn some of the lessons of the past. Ex ante studies can provide information to assist in the allocation of scarce research resources to activities that best match donors’ development objectives. In practice, impact assessment is often contentious and almost always difficult, particularly when livestock are involved. In this paper, we outline methods that can be used in ex ante impact assessment, and illustrate some of these in relation to three recent studies on improved food-feed crops in different places: improving the quality of millet and sorghum stover in India, using dual-purpose cowpea in West Africa, and alternatives for utilizing maize stover in the mixed systems of East and Southern Africa. Such impact assessments are neither cheap nor quick, and the methods that are most appropriate in any situation will depend not only on the resources and expertise available but most importantly on the exact nature of the questions being asked and the end-users of the results. Much remains to be done to maximize the utility of such assessments, particularly in the areas of quantitative model development, rapid qualitative method development, more effective integration of biophysical and socio-cultural indicators and approaches, and provision of baseline data against which to measure progress. Research resource allocation may well retain its somewhat haphazard nature in the future, but given the challenges facing agriculture in developing countries, a mechanism for attempting to ensure that research and extension really do contribute to widely held development goals has to be based on more than trial and error.